(untitled) (International Journal of Food and Nutritional Sciences, 2022)
A series of Bis-Phthalimides derivatives was synthesized and characterized by physicochemical and spectral means. The synthesized compounds were evaluated for in-vitro antimicrobial activity against Staphylococcus aureus and Escherichia coli by tube dilution method. The most promising antimicrobial activity of derivatives (K1H and K5H) was further docked to study their binding efficacy to the active site of Code 1KZN. All the compounds possessed significant antimicrobial activity with MIC in the range of 40μg/ml to 80μg/ml. The molecular docking studies of potent antimicrobial compounds (PMO, K1H and K5H) showed their putative binding mode and significant interactions with DNA gyrase subunit b as prospective agents.